The Spin Voltage Enhancement in Si/YIG/Co, Fe Spin Hall Thermopiles - Wimutti Kumpor; Perawas Kuptapol; Chalothon Wongjom; Ekkarat Pongophas; Yingyot Infahsaeng; Wasan Maiaugree; Santi Phumying; Rungrueang Pattanakul; Mati Horprathum; Chanunthorn Chananonnawathorn; Piyawat Piyasin; Supree Pinitsoontorn; et al. (Journal of Engineering, 2024)
Spin‐Hall thermopiles have been previously proposed as a means to enhance the spin Seebeck effect (SSE). However, the use of platinum (Pt) for spin detection drives costs high and proves an impediment for scalability. In this work, a cost‐effective spin‐Hall thermopile constructed from opposite spin‐Hall angle ferromagnets, cobalt (Co) and iron (Fe), is reported. The devices are fabricated using a standard sputter‐coated yttrium iron garnet (YIG) substrate that serves as the spin injector, and thermally evaporated Co and Fe strips that enable spin detection. When serially connected to form a (YIG/Co, Fe) thermopile structure, measurements indicate a significant enhancement of the spin voltage that results from the additive spin contributions of the opposite spin‐Hall angle ferromagnets and the anomalous Nernst effect (ANE) that they exhibit. The YIG/Co, Fe thermopile reported here offers a cost‐effective alternative to Pt‐based thermopiles and the possibility of large‐scale implementation to realize future thermoelectric generators.
Keywords: Magnetic properties of thin films; Magneto-Optical Properties and Applications; Quantum and electron transport phenomena